PROBLEMS OF STRUCTURAL DEVELOPMENT OF ECONOMY IN ARMENIA - Saribekyan, Amalya (Bulletin of Yerevan University G: Economics, 2025)
Today’s global economy is characterized by acceleration of technological changes, market rate fluctuations and increasingly growing competition. For their in-dept understanding, we need to review the structural developments in the economy, in particular, the mutual interaction between the economic structure – value added – economic growth and development and in this context, reveal the structural development challenges. To this end, we have analyzed the developments in the Armenian economy, its sectors and sub-sectors in parallel to modern structural shifts. The obtained results may become guidelines for efficient interaction between various structural units and future robust economic growth.